Antimicrobial Peptides-based Nanostructured Delivery Systems: An Approach for Leishmaniasis Treatment - Rodríguez-Carlos, Adrian; Martinez-Gutierrez, Fidel; Torres-Juarez, Flor; Rivas-Santiago, Bruno (Current Pharmaceutical Design, 2019)
Background: Leishmaniasis is a major health problem mainly in tropical and subtropical areas worldwide, although in the last decades it has been treated with the use of conventional drugs such as amphotericin, the emergence of multidrug-resistant strains has raised a warning signal to the public health systems thus a new call for the creation of new leishmanicidal drugs is needed. Methods: The goal of this review was to explore the potential use of antimicrobial peptides-based nanostructured delivery systems as an approach for leishmaniasis treatment. Results: Within these new potential drugs, human host defense peptides (HDP) can be included given their remarkable antimicrobial activity and their outstanding immunomodulatory functions for the therapy of leishmaniasis. Conclusion: Though several approaches have been done using these peptides, new ways for delivering HDPs need to be analyzed, such is the case for nanotechnology.
Keywords: nanoparticles